Symbolism and Meaning in Old Masjid Architecture of Malay Archipelago: A Case Study of Masjid in Kerinci, Jambi, Indonesia-presentation - Abdul Rahim, Zaiton; Mohd Nawawi, Norwina; Denan, Zuraini; Abdul Majid, Noor Hanita; Abdullah, Fadzidah (2019)
Masjid (mosque) plays a significant role in the life of a Muslim. Throughout history, the old masjids of the old cities and towns reflect the acculturation of Islamic faith with the local culture that embraced the religion. This paper demonstrates through experiential learning how acculturation of Islamic faith and culture of the people in the Malay Archipelago gives symbolic meanings to the masjid architecture and enhances the spatial as well as the spiritual experience of the people. The old masjid in the Kerinchi region of Sumatra, Indonesia, was selected as the case studies. In the process of the research, important aspects of the religion and culture were encoded, presented and communicated in the form of architectural features of the masjid, giving meanings and heightened the spiritual experience of the users. The symbolic meanings made through architectural manifestation, in physical form, both structural and non-structural components of the masjid, enriches and gives a distinctive and unique character to the masjid architecture. The symbolic meanings in the old masjid architecture of Kerinci are simplified abstractions to manifest the worldview of the local people based on the spirit of Islam. The paper concluded that incorporating symbolism that does not impede Islamic teachings or the shariah in designing a masjid can enhance and even exalted the religious spirit of users while providing distinct character to the masjid. Old masjids are the best example of how architecture can play a significant role is not only as a focal congregational space for the daily worshippers but can also enhance their spiritual experiences. In the same process, the physical masjid naturally creates an identity to the place -charmingly.